Design And CFD Analysis of A 250 Kg Capacity Boat For Access Between Small Islands In The Lampung Tourism Area - Nazarrudin, Rizal; Sabiqunassabiqun (INSTEP Network, 2024)
Characteristics from design boat capacity 3-4 people or 250 kg good for used access between island small in area tour with depth shallow base. The resistance of the boat's hull when operating plays an important role in knowing the power required by the boat. This is very important in designing a hull. Therefore, in design This will be done in numerical simulation using Computational Fluid Dynamics (CFD) to know how much power is required by the boat with a number of variation speeds. Design simulation moreover formerly created in Autodesk Inventor software, then design that has been designed will be simulated using the Ansys Fluent CFD application program. The data variables used in simulation numeric using varying speed limits namely 20 knots, 16 knots, 12 knots, 8 knots, and 4 knots, as well as condition rate flow is turbulent, wall side and top is symmetry, and the part the design that will be simulated is part hull the boat that sank in the water. The result of simulation numeric boat 250 kg capacity indicates a number of pressure and velocity contours of part hull as well as obtained Power highest at a speed of 20 knots 13938.511 Watts.